Global Analysis of Viral Infection in an Archaeal Model System - Maaty, Walid S.; Steffens, Joseph; Heinemann, Joshua; Ortmann, Alice C.; Reeves, Benjamin D.; Biswas, Swapan K.; Dratz, Edward A.; Grieco, Paul A.; Young, Mark J.; Bothner, Brian (Frontiers in Microbiology, 2012)
The origin and evolutionary relationship of viruses is poorly understood. This makes archaeal virus-host of particular interest because the hosts generally root near the base of phylogenetic trees, while some of the viruses have clear structural similarities to those that infect prokaryotic and eukaryotic cells. Despite the advantageous position for use in evolutionary studies, little is known about archaeal viruses or how they interact with their hosts, compared to viruses of bacteria and eukaryotes. In addition, many archaeal viruses have been isolated from extreme environments and present a unique opportunity for elucidating factors that are important for existence at the extremes.. In this article we focus on virus-host interactions using a proteomics approach to study Sulfolobus Turreted Icosahedral Virus (STIV) infection of Sulfolobus solfataricus P2. Using cultures grown from the ATCC cell stock, a single cycle of STIV infection was sampled 6 times over a 72 hr period. More than 700 proteins were identified throughout the course of the experiments. Seventy one host proteins were found to change by nearly two-fold (p<0.05) with 40 becoming more abundant and 31 less abundant. The modulated proteins represent 30 different cell pathways and 14 COG groups. 2D gel analysis showed that changes in post translational modifications were a common feature of the affected proteins. The results from these studies showed that the prokaryotic antiviral adaptive immune system CRISPR associated proteins (CAS proteins) were regulated in response to the virus infection. It was found that regulated proteins come from mRNAs with a shorter than average half-life. In addition, activity-based protein profiling (ABPP) profiling on 2D gels showed caspase, hydrolase and tyrosine phosphatase enzyme activity labeling at the protein isoform level. Together, this data provides a more detailed global view of archaeal cellular responses to viral infection, demonstrates the power of qua